Role of Cholesterol‐Associated Steatohepatitis in the Development of NASH. Issue 1 (24th August 2021) - Horn, Christian L.; Morales., Amilcar L.; Savard, Christopher; Farrell, Geoffrey C; Ioannou, George N.
Abstract : The rising prevalence of nonalcoholic fatty liver disease (NAFLD) and NAFLD‐related cirrhosis in the United States and globally highlights the need to better understand the mechanisms causing progression of hepatic steatosis to fibrosing steatohepatitis and cirrhosis in a small proportion of patients with NAFLD. Accumulating evidence suggests that lipotoxicity mediated by hepatic free cholesterol (FC) overload is a mechanistic driver for necroinflammation and fibrosis, characteristic of nonalcoholic steatohepatitis (NASH), in many animal models and also in some patients with NASH. Diet, lifestyle, obesity, key genetic polymorphisms, and hyperinsulinemia secondary to insulin resistance are pivotal drivers leading to aberrant cholesterol signaling, which leads to accumulation of FC within hepatocytes. FC overload in hepatocytes can lead to ER stress, mitochondrial dysfunction, development of toxic oxysterols, and cholesterol crystallization in lipid droplets, which in turn lead to hepatocyte apoptosis, necrosis, or pyroptosis. Activation of Kupffer cells and hepatic stellate cells by hepatocyte signaling and cholesterol loading contributes to this inflammation and leads to hepatic fibrosis. Cholesterol accumulation in hepatocytes can be readily prevented or reversed by statins. Observational studies suggest that use of statins in NASH not only decreases the substantially increased cardiovascular risk, but may ameliorate liver pathology. Conclusion: Hepatic FC loading may result in cholesterol‐associated steatohepatitis and play an important role in the development and progression of NASH. Statins appear to provide significant benefit in preventing progression to NASH and NASH‐cirrhosis. Randomized controlled trials are needed to demonstrate whether statins or statin/ezetimibe combination can effectively reverse steatohepatitis and liver fibrosis in patients with NASH. Abstract : Free cholesterol accumulates in the liver in some patients with NAFLF and promotes the necroinflammation and fibrosis typical of NASH. Cholesterol‐associated steatohepatitis (CASH) plays an important role in the development and progression of NASH. Randomized controlled trials are needed to demonstrate whether statins or statin/ezetimibe combination can effectively reverse steatohepatitis and liver fibrosis in patients with NASH.